PENGARUH PEMBERIAN TES FORMATIF TERHADAP PENINGKATAN HASIL BELAJAR PENDIDIKAN KESEHATAN PADA SISWA KELAS VII SMP NEGERI 2 KRIAN - KHAFID, MOCHAMMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Submission of material on the subjects of Physical Education, Sport and Health in schools, generally just put physical activity top priority such as the development of basic movement and improvement of physical fitness, so that the delivery of material tend not to appropriate to the Standards of Competence (SC) and the Basic Competency (BC) subjects Physical Education, Sport and Health One material that is often overlooked is the health education. This is consistent with the observation on junior high school 2 Krian that the delivery of health education materials on Penjasorkes subjects tend to be neglected, so that the form of cognitive assessment formative test was never performed. The purpose of this study was to determine the effect of formative tests to increased health education learning outcomes in class VII student of SMP Negeri 2 Krian and to determine the magnitude of the effect of formative tests to the improvement of learning outcomes in the health education class VII student of Junior High School  2 Krian. This research is a descriptive approach through quantitative experiments. Research design used is Randomized Control Group Pretest-Posttest Design. The population in this study is a class VII student of Junior High School  2 Krian totaled 360 students consisting of 10 classes. Sampling using cluster random sampling is a class VII-D as an experiment group with a number of 35 students and VII-I as a control group by the number of 36 students. Based on the analysis of different test with different sample, obtained significance value of 0.170 for pretest calculations the control and experiment. Based on the analysis of data known to an increase in health education learning outcomes in the control group was 18.79 %, while the increase in health education learning outcomes in the experiment group was 32.22 %, so the percentage increase in health education learning outcomes in the experiment group is higher 13.43 % of the control group. From the calculation results of different test with different sample (independent sample t-test) obtained significance value of 0.030 <ρvalue (sig) 0.05 then the hypothesis is accepted. Thus it can be concluded that there is a significant effect of giving formative test to increase  learning outcomes health education  to students in class VII of  junior high school 2 Krian. Keywords: formative tests, learning outcomes, health education